Indian Stock Market’s Response in Five - Phases to the COVID-19 Pandemic - Dey, Kushal; Brown, Ayan (Indian Journal of Research in Capital Markets, 2021)
The Covid-19 pandemic has affected the health as well as the financial and economic well-being of India and the world from the beginning of the year 2020. This research committed to investigate the response of critical indices in BSE and NSE to the Covid-19 pandemic in India and also its impact on five sectorial indices on S&P BSE Sensex. This research examined and analyzed the daily closing prices of stock indices in five identified phases in the year 2020 (272 days of trading). Moving average method of stock volatility measurement was used to analyze market data in the five - phases to capture the volatility and present in a formal manner. This study took into consideration the entire time span of the Covid-19 pandemic from its onset until the end of the first wave to witness the true nature of volatility in stock prices and graphically represented the instability that existed throughout the year 2020. After careful analysis, the findings showed that just as fast the Indian stock market experienced a situation of high panic during the onset with high volatility, it recovered from instability with reduced volatility as pre-Covid conditions in the later phases and also surged to cross the 50,000 mark in the shortest time by February 2021.